Teachers’ mathematical knowledge for teaching in relation to the inclusion of history of mathematics in teaching - Smestad, Bjørn; Jankvist, Uffe Thomas; Clark, Kathleen (NOMAD Nordic Studies in Mathematics Education, 2014)
This article discusses how the inclusion of history of mathematics in mathematics education draws heavily on a teacher’s mathematical knowledge for teaching, in particular horizon content knowledge, in the context of curricular changes. We discuss the role of history of mathematics in school curricula, its inclusion in textbooks and its consequences for the mathematical knowledge needed for teaching. We address the matter from three national settings (Denmark, Norway and the United States). These settings exemplify how, in particular, teachers’ horizon content knowledge needs to be broader than what is necessary for only the current curriculum.